A Collaborative Program for the 2020 great Solar Eclipse in Argentina - Basset, Ana Maria (2021)
This contribution presents the preparation, actions and experience related with the Total Solar Eclipse on Dec 14th, 2020 in Argentina. The event in a pandemic year, was followed for millions of persons virtually, but inside the totality path and beyond, the citizens scientists and teachers were the protagonists.